2000
DOI: 10.1046/j.1365-2915.2000.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Sampling methods for phlebotomine sandflies

Abstract: Abstract. A review is presented of methods for sampling phlebotomine sand¯ies (Diptera: Psychodidae). Among~500 species of Phlebotominae so far described, mostly in the New World genus Lutzomyia and the Old World genus Phlebotomus, about 10% are known vectors of Leishmania parasites or other pathogens. Despite being small and fragile, sand¯ies have a wide geographical range with species occupying a considerable diversity of ecotopes and habitats, from deserts to humid forests, so that suitable methods for coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
200
1
17

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(224 citation statements)
references
References 86 publications
6
200
1
17
Order By: Relevance
“…Although light traps have been commonly used for the collection of sand ßies (Hilmy et al 1989, Kaul et al 1994, Robert et al 1994, Alexander 2000, Orndorff et al 2002, few studies have compared them to landing and/or biting collections. Alexander (2000) reported that a potential disadvantage of light traps was that they might preferentially sample females of certain species that are highly phototropic and suggested that light traps had limited value in ecological studies of sand ßies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although light traps have been commonly used for the collection of sand ßies (Hilmy et al 1989, Kaul et al 1994, Robert et al 1994, Alexander 2000, Orndorff et al 2002, few studies have compared them to landing and/or biting collections. Alexander (2000) reported that a potential disadvantage of light traps was that they might preferentially sample females of certain species that are highly phototropic and suggested that light traps had limited value in ecological studies of sand ßies.…”
Section: Discussionmentioning
confidence: 99%
“…Although light traps have been commonly used for the collection of sand ßies (Hilmy et al 1989, Kaul et al 1994, Robert et al 1994, Alexander 2000, Orndorff et al 2002, few studies have compared them to landing and/or biting collections. Alexander (2000) reported that a potential disadvantage of light traps was that they might preferentially sample females of certain species that are highly phototropic and suggested that light traps had limited value in ecological studies of sand ßies. However, Fryauff and Modi (1991) and Davies et al (1995) determined that light trap collections were comparable to biting collections for P. papatasi in Egypt and sand ßies in the Peruvian Andes, respectively, whereas Rioux et al (1982) reported that adhesive traps provided results similar to human bait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sand flies 3-4 days old were used in all experiments, since in preliminary observations, we found that females fed well at that age. On the day of the experiment, female sand flies were counted and transferred using a Castro aspirator (Sherlock & Pessoa 1964, Alexander 2000 into two separate larger plaster-lined pots measuring approximately 1500 cm 3 and kept in styrofoam containers with moist cotton wool to keep the humidity high for transport. The females were transferred into large cubic net cages 10-15 min before the anesthetised dogs were placed inside the nets.…”
Section: Methodsmentioning
confidence: 99%
“…Nessas armadilhas um ou mais frascos contendo líquido fi xador ou vapores tóxicos são acoplados na parte superior, onde os insetos são aprisionados (Alexander 2000).…”
Section: Palavras-chave: Phlebotominae Leishmaniose Vetorunclassified